Evaluation of commercial soft contact lenses for ocular drug delivery: A review. (1st October 2020) - Fan, Xin; Torres-Luna, Cesar; Azadi, Marjan; Domszy, Roman; Hu, Naiping; Yang, Arthur; David, Allan E.
Abstract: Soft contact lenses have generated growing interest in ocular drug delivery due to their potential to enhance drug bioavailability in ocular tissues. Commercially available soft contact lenses offer several advantages for ocular drug delivery as they are manufactured on a large scale, which guarantees the availability of a consistent and reproducible product, and their favorable safety profile is well-established through broad clinical use. Here we review the rationale for using commercially available soft contact lenses for ocular drug delivery; summarize the evolution of the materials used in contact lens fabrication; and explore various methods used to improve the drug release characteristics and its tissue penetration. While significant progress has been made, several issues still require further attention for the commercial launch of a viable drug-eluting contact lens product, including control of initial burst release, shelf-life stability, and drug loss during processing or storage. Graphical abstract: Image, graphical abstract